Postgraduate education at the Juan José Apolinaire Pennini polyclinic in Cienfuegos - Marisela García de la Torre; Dayme Rodríguez Fumero; Zulema González Abreu; Grisel Vidal Cabrera; Carlos Manuel Crespo Tamayo (Medisur)
Background: postgraduate education constitutes the upper stage of the educational cycle and responds to the need to train human resources of the highest level, both professionally, as well as in teaching and research. Objective: to describe the medical graduates’ postgraduate education at the Juan José Apolinaire Pennini polyclinic, in Cienfuegos. Methods: descriptive cross-sectional research carried out from January to May 2022. The analyzed variables were: academic training, years of graduation, specialization, teaching category, scientific category and professional improvement. Results: 69.76% of the graduates are first degree specialists; Graduates with more than 11 years of experience prevailed (51.16%), second degree specialists represented 4.65% and master's degrees 16.27%. Comprehensive General Medicine specialists predominated (54.65%). 100% of the graduates received improvement courses, 20.93% have a teaching category and 3.8% have a scientific researcher category. Conclusions: postgraduate education is developed continuously. Strengths were identified such as the prevalence of specialists in Comprehensive General Medicine with more than 11 years of graduation, the basic work group completion with categorized professors who participate in academic training and professional improvement that is developed satisfactorily. There are insufficiencies in the second degree specialists training, masters and doctors of science; In addition, there is no correspondence between the number of graduates and the teaching research categories.